ANALISIS PROBLEMATIKA KOPERASI SARANGAN ASRI UNTUK PENINGKATAN EKONOMI ANGGOTA PADA NEW NORMAL - Bara Septian Laraswati; Suprih Hartanto; Moh. Irmawan Jauhari (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2022)
This activity aims to map the problems of the Sarangan Asri Cooperative to improve the member's economy in the new normal. The result of the activity is that there are four things related to cooperative problems in the new normal. First, in the economic field, it was found that the problem of decreasing member turnover was due to the lack of visitors, the turnover of membership dues decreased due to reduced income, loans brought by cooperative members were difficult to withdraw considering the difficulties during the pandemic, and many cooperative members opened other businesses to wait for the pandemic to end. Second, in the field of human resources, cooperative management requires administrative management development and cooperative members require business innovation training. Third, in the cooperative culture, it is known that members and administrators are passive in responding to changes that occur and the second is lack of innovation. The passivity that occurs is not without reason considering several factors such as the busyness of the traders who are members and administrators of the cooperative. Fourth, support from stakeholders and policy makers is lacking. In this case, the focus of the government and various parties is indeed focused on the completion of the COVID-19 pandemic.